Vitamin D deficiency and Body Mass Index- A Hospital-based correlation study - Deepa S Sajjanar; G V Naregal; B B Devaranavadagi (Wolters Kluwer Medknow Publications, 2020)
Background: Vitamin D deficiency (VDD) has become a pandemic and is a bigger concern even in sunny location as the region of north Karnataka, India. The present study is aimed to evaluate the prevalence of VDD and its correlation with BMI in the regional population if any. Methods: Relevant data of subjects in the age group of 18-60 years including serum 25(OH) Vitamin D levels was registered. Data was analyzed using SPSS software v.23.0 and Microsoft office 2007. Chi-square (χ2) test was used to test association. Results: The prevalence of VDD (25(OH) D < 50 nmol/L) was more in the older (51-60 years) age group showing a preponderance in the rural population. However, even the young population and those of normal BMI had a considerable deficiency of vitamin D. Significant association was found only between vitamin D levels and age. Conclusion: VDD is highly prevalent in this region, irrespective of age, BMI, and urban/rural settings. The data can aid the treating physicians to appreciate the gravity of the pandemic and formulate policies to improve the vitamin D status in the community.